2007
DOI: 10.1016/j.pmpp.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The spore coat of the bean anthracnose fungus Colletotrichum lindemuthianum is required for adhesion, appressorium development and pathogenicity

Abstract: The spores (conidia) of the bean anthracnose fungal pathogen, Colletotrichum lindemuthianum, adhere to the aerial parts of plants to initiate the infection process. In previous studies we have shown that the Colletotrichum spores are surrounded by a fibrillar spore coat, comprising several major glycoproteins. Previous evidence showed that a monoclonal antibody (UB20) that recognised these glycoproteins was able to inhibit adhesion of spores to a hydrophobic surface. In this paper we have further studied the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…These structures can vary greatly in morphology and the complete cycle varies in duration from less than 24 h to over 3 d (Perfect et al 2001). The spherical vesicles shown in this study are also found in P. vulgaris against Colletotrichum lindemuthianum (Rawlings et al 2007) and in cucumber against C. orbiculare (Asakura et al 2012). However, this structure differs morphologically from that of Colletotrichum destructivum, which does not develop spherically, but rather as swollen multilobed vesicles during infection (Shen et al 2001).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…These structures can vary greatly in morphology and the complete cycle varies in duration from less than 24 h to over 3 d (Perfect et al 2001). The spherical vesicles shown in this study are also found in P. vulgaris against Colletotrichum lindemuthianum (Rawlings et al 2007) and in cucumber against C. orbiculare (Asakura et al 2012). However, this structure differs morphologically from that of Colletotrichum destructivum, which does not develop spherically, but rather as swollen multilobed vesicles during infection (Shen et al 2001).…”
Section: Discussionsupporting
confidence: 51%
“…In contrast to SA treatment, although there was long germ-tube formation in GO/G-treated leaves, appressorial formation was accompanied by melanization ( Fig 4D). As previously described (Perfect et al1999;Wharton & Di eguez-Uribeondo 2004;Rawlings et al 2007) during this process, the conidium adheres to the cuticle and germinates, producing a germ-tube that differentiates into melanized appressoria. After melanization, a narrow penetration hypha emerges at the base of the appressorium and subsequently penetrates directly into the cuticle, forming biotrophic vesicles and primary hyphae (M€ unch et al 2008).…”
Section: Discussionmentioning
confidence: 70%
“…However, UB20 treatment did not affect appressorium formation and pathogenicity. The conidium adhesion deficiency was compensated after germination, suggesting that germ tube adhesion was involved in appressorium formation and pathogenicity (Rawlings et al, 2007).…”
Section: Colletotrichum Speciesmentioning
confidence: 99%
“…Canopy moisture also played an important role in disease transmission, which agrees with previous work (Schwartz et al 2005). Canopy moisture increased the disease severity, particularly with the natural inoculum source, which may be due to an interaction with the mucilaginous sheath surrounding the spores (Rawlings et al 2007). The results of the current study indicate that a natural source of inoculum tended to fall between the two concentrations of artificial inoculum in relation to disease severity, although no attempt was made to determine the spore concentration of the natural inoculum source.…”
Section: Seed Pickmentioning
confidence: 99%
“…Each spore and germ tube is surrounded by a mucilaginous sheath, thought to aid in the attachment of the appressoria to the plants surface (Young and Kauss 1984;Nicholson et al 1992;Perfect et al 1999). Removal of the sheath inhibits adhesion of the spores to plants (Rawlings et al 2007). This sheath is composed of proline-rich glycoproteins that contain germination inhibitors (Young and Kauss 1984;Nicholson et al 1992).…”
mentioning
confidence: 99%